Experimental investigation on magnetorheological finishing process parameters - Abdul Wahab, Hashmi; Mali, Harlal Singh; Meena, Anoj; Khilji, Irshad Ahamad; Chilakamarry, Chaitanya Reddy; Siti Nadiah, Mohd Saffe (Elsevier Ltd, 2022)
Magneto-rheological polishing (MRP) fluid was developed by MR fluid using a magnetic field, non-magnetic abrasives such as SiC and Al2O3, and carrier medium like oil. A magnetic polishing tool was developed using a super-strong permanent neodymium magnet (Nd2Fe14B) with 0.5-tesla magnetic intensity. This polishing tool was assembled to the vertical milling machine for the finishing workpieces. In the present research, magnetic materials (steel material) and non-ferromagnetic (copper) content were finishing using a developed MRP setup for experimental investigation. This research also investigated the parametric dependencies of different abrasives on the magneto-rheological finishing process. It determined the effect of magnetic particle concentration and abrasives on the surface roughness of ferromagnetic (stainless steel) and non-ferromagnetic material (copper). The final surface roughness value has reached 30 nm from its initial surface roughness of 800 nm for non-ferromagnetic (copper). For the magnetic material (stainless steel), the value is 50 nm from 1300 nm.